ChemInform Abstract: Organocatalytic Entry into 2, 6‐Disubstituted Aza‐Achmatowicz Piperidinones: Application to (‐)‐Sedacryptine and Its Epimer. Issue 37 (16th September 2014) - van der Pijl, Ferdi; Harmel, Robert K.; Richelle, Gaston J. J.; Janssen, Peter; van Delft, Floris L.; Rutjes, Floris P. J. T.
Abstract (‐)‐Sedacryptine (XIII) and its epimer (XVI) are prepared via organocatalyzed Mannich, aza‐Achmatowicz, and an N‐acyliminium ion addition reaction from boc‐protected furanyl amines.